Challenges and applications of isotachophoresis coupled to mass spectrometry: A review. Issue 12 (6th April 2020) - Melzer, Tanja; Wimmer, Benedikt; Bock, Stephanie; Posch, Tjorben Nils; Huhn, Carolin
Abstract: Electrophoretic separations are of growing interest to tackle complex analytical challenges. Nevertheless, capillary electrophoresis, as the most common mode, still suffers from insufficient detection limits due to low capillary loadability. ITP is of growing interest as preconcentration method for capillary electrophoresis and is also interesting to be applied as an independent analytical method. While mass spectrometric detection is common for capillary electrophoresis, the combination of ITP with MS is still a niche technique. In this work, we want to give an overview on isotachophoretic effects in CE‐MS and ITP‐MS methods, as well as coupling techniques of ITP with CE‐MS. The challenges and possibilities associated with mass spectrometric detection in ITP and its coupling to capillary electrophoresis are critically discussed.